Studi komparasi antara pembelajaran problem solving dengan discovery learning terhadap kemampuan komunikasi matematis siswa - Lestari, Dini Anggi; Sormin, Masdelima Azizah; Samosir, Benny Sofyan (Karoteh Utama, 2024)
This study aims to compare the effects of the Problem Solving and Discovery Learning models on students' mathematical communication skills in grade XI at SMA Aliyah-Washliyah 36 Serbelawan. The sample was randomly selected using random sampling techniques, with class XI MIA I employing the Problem Solving model and class XI MIA II utilizing the Discovery Learning model. Data were collected through observation, documentation, and tests, then analyzed using statistical tests to examine the research hypothesis. The results showed that both learning models had a significant effect on students' mathematical communication skills. The average score for the Problem Solving model was 1.99, while the Discovery Learning model achieved 2.19, indicating a significant difference between the two. This study concludes that both Problem Solving and Discovery Learning are effective in enhancing students' mathematical communication skills, with Discovery Learning yielding slightly better results. These findings recommend teachers select suitable learning models based on students' needs.